2014
DOI: 10.1007/s11060-014-1652-6
|View full text |Cite
|
Sign up to set email alerts
|

Single agent vinorelbine in pediatric patients with progressive optic pathway glioma

Abstract: The management of progressive unresectable low-grade glioma remains controversial. Treatment options have included radiotherapy, and more recently chemotherapy, usually following an initial period of observation. Within this context, we evaluated vinorelbine, a semi-synthetic vinca alkaloid that has shown evidence of activity against glioma. From July 2007 an institutional protocol with vinorelbine (30 mg/m(2) days 0, 8, 22) for a total of 18 cycles, has been conducted at IOP/GRAACC/UNIFESP for children with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…Recently, investigators have suggested that the use of frontline chemotherapy in pediatric low-grade glioma may be associated with inferior visual outcomes and progression-free survival. 21,[29][30][31][32] Our data do not support this finding. Nonetheless, our data suggest that the therapeutic ratio of proton therapy within the first 5 years of treatment compares favorably with contemporary chemotherapy options.…”
Section: Freedom From Event (%)contrasting
confidence: 94%
See 1 more Smart Citation
“…Recently, investigators have suggested that the use of frontline chemotherapy in pediatric low-grade glioma may be associated with inferior visual outcomes and progression-free survival. 21,[29][30][31][32] Our data do not support this finding. Nonetheless, our data suggest that the therapeutic ratio of proton therapy within the first 5 years of treatment compares favorably with contemporary chemotherapy options.…”
Section: Freedom From Event (%)contrasting
confidence: 94%
“…Nonetheless, our data suggest that the therapeutic ratio of proton therapy within the first 5 years of treatment compares favorably with contemporary chemotherapy options. 29,30 If this result bears out over longer follow-up and proton therapy becomes more widely available, re-examination of the role of chemotherapy (and socalled systemic "targeted agents") within the algorithm of pediatric LGG management may be warranted. Perhaps one day a 5-year-old child with a new diagnosis will need not undergo 3 (or more) cycles of chemotherapy and their associated toxicity before curative radiation, a strategy pursued in 13% of the patients in our series.…”
Section: Freedom From Event (%)mentioning
confidence: 99%
“…As well, a small series investigated the combination of bevacizumab and irinotecan, vinorelbine or temozolomide [37], [38], [39], [40], [41], [42]. Efficacy was judged by assessing radiological tumour response, while survival (OS) and progression-free survival (PFS) data were not always available.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving to maintain sustained stable disease in pediatric patient with LGG, while limiting both acute and long-term toxicities is challenging [2][3][4][5][6][7][8][9][10]. Recently, the combination of bevacizumab and irinotecan has been reported to produce rapid tumor response in some children with recurrent LGG [3][4][5][6], but patients frequently relapse shortly after stopping treatment [4].…”
Section: Discussionmentioning
confidence: 99%